History and Virtual Topology: The Nineteenth-Century Press as Material Flow - Nivala, Asko; Salmi, Hannu; Sarjala, Jukka (Historein, 2018)
Drawing on a new materialist approach, this article discusses the concepts of the virtual and virtual topology, and their fruitfulness for historians' empirical work. It starts by following Gilles Deleuze's argument that the virtual, the transformative potential of the real, has to be distinguished from the possible, which is merely an imagined double of the given world. Embracing this premise, the article shows the potential of virtual topology to shed light on the transformation of a network in the past. It suggests that history is not only about actual and stable things, it is also a site of becomings. This idea is elaborated through an analysis that focuses on the changes in the nineteenth-century Finnish press. The virtual as a theoretical concept is combined with the methodological opportunities offered by recent developments in the digital humanities, in this case, text reuse detection.